ΑB‐Crystallin regulates expansion of CD11b+Gr‐1+ immature myeloid cells during tumor progression. Issue 1 (2nd October 2012) - Dieterich, Lothar C.; Schiller, Petter; Huang, Hua; Wawrousek, Eric F.; Loskog, Angelica; Wanders, Alkwin; Moons, Lieve; Dimberg, Anna
Abstract : The molecular chaperone αB‐crystallin has emerged as a target for cancer therapy due to its expression in human tumors and its role in regulating tumor angiogenesis. αB‐crystallin also reduces neuroinflammation, but its role in other inflammatory conditions has not been investigated. Here, we examined whether αB‐crystallin regulates inflammation associated with tumors and ischemia. We found that CD45 + leukocyte infiltration is 3‐fold increased in tumors and ischemic myocardium in αB‐crystallin‐deficient mice. Notably, αB‐crystallin is prominently expressed in CD11b + Gr‐1 + immature myeloid cells (IMCs), known as regulators of angiogenesis and immune responses, while lymphocytes and mature granulocytes show low αB‐crystallin expression. αB‐Crystallin deficiency results in a 3‐fold higher accumulation of CD11b + Gr‐1 + IMCs in tumors and a significant rise in CD11b + Gr‐1 + IMCs in spleen and bone marrow. Similarly, we noted a 2‐fold increase in CD11b + Gr‐1 + IMCs in chronically inflamed livers in αB‐crystallin‐deficient mice. The effect of αB‐crystallin on IMC accumulation is limited to pathological conditions, as CD11b + Gr‐1 + IMCs are not elevated in naive mice. Through ex vivo differentiation of CD11b + Gr‐1 + cells, we provide evidence that αB‐crystallin regulates systemic expansion of IMCs through a cell‐intrinsic mechanism. Our study suggests a key role of αB‐crystallin in limiting expansion of CD11b + Gr‐1 + IMCs in diverse pathological conditions.—Dieterich, L. C., Schiller, P., Huang, H., Wawrousek, E. F., Loskog, A., Wanders, A., Moons, L., Dimberg, A. αB‐Crystallin regulates expansion of CD11b + Gr‐1 + immature myeloid cells during tumor progression. FASEB J. 27, 151–162 (2013). www.fasebj.org